2020
DOI: 10.1007/s10557-020-06989-9
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin Protects Cardiac Mitochondrial Fatty Acid Metabolism in a Mouse Model of Diet-Induced Lipid Overload

Abstract: Purpose. Sodium-glucose cotransporter 2 (SGLT2) inhibitors prevent heart failure and decrease cardiovascular mortality in patients with type 2 diabetes. Heart failure is associated with detrimental changes in energy metabolism, and the preservation of cardiac mitochondrial function is crucial for the failing heart. However, to date, there are no data to support the hypothesis that treatment with a SGLT2 inhibitor might alter mitochondrial bioenergetics in diabetic failing hearts. Thus, the aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Studies have shown significant heterotopic lipid deposition in the renal tubules in DN, and empagliflozin improves lipid metabolism abnormalities in DN and other diseases. [16][17][18][19] Empagliflozin improves endothelial function, reduces atherosclerosis, and restores vascular tension in patients with type 2 diabetes. Additionally, empagliflozin relieves muscle pain and weakness and alleviates non-alcoholic fatty liver disease in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown significant heterotopic lipid deposition in the renal tubules in DN, and empagliflozin improves lipid metabolism abnormalities in DN and other diseases. [16][17][18][19] Empagliflozin improves endothelial function, reduces atherosclerosis, and restores vascular tension in patients with type 2 diabetes. Additionally, empagliflozin relieves muscle pain and weakness and alleviates non-alcoholic fatty liver disease in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Although controversial depending on the study setting, most agree that MI-induced failing heart leads to a decrease in fatty acid use with a corresponding increase in glucose utilization. This suggestion is supported by the growing list of others who have shown that gliflozin class drugs help to maintain the heart’s preference for utilizing fatty acids and ketone bodies [ 15 , 43 , 44 , 45 ]. However, in most cases heart failure is associated with a decrease in overall cardiac energetics [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 90%
“…Metabolic remodeling is closely related to the occurrence and development of cardiac hypertrophy and other heart diseases. Exploring the energy metabolism mechanism of cardiomyocytes may lead to new therapeutic targets, which will be helpful to design new effective methods and strategies for the treatment of heart failure ( Bøgh et al., 2020 ; Makrecka-Kuka et al., 2020 ; Zuurbier et al., 2020 ). As we all know, physical exercise has a protective effect on the heart, and can even partially compensate for heart damage and improve heart function.…”
Section: Discussionmentioning
confidence: 99%